Convergent and Practical Synthesis of Fluorescent Triphenylamine Derivatives and Their Localization in Living Cells. Issue 2 (14th January 2022) - Mougeot, Romain; Oger, Samuel; Auvray, Marie; Gallavardin, Thibault; Leleu, Stéphane; Mahuteau‐Betzer, Florence; Franck, Xavier
Abstract: In the search for new fluorescent triphenylamine (TP) derivatives, we studied the influence of the position and substitution of diverse heterocyclic substituents. A library of 10 fluorescent triphenylamines bearing either oxazoles or thiazoles and pyridiniums, substituted at different positions has been developed. The approach is based on a convergent C−H activation reaction between pyridine‐oxazoles or pyridine‐thiazoles and di‐iodo triphenylamine. We showed that the nature and substitution pattern of the 5‐membered‐ (oxazole, thiazole) or 6‐membered heterocycle (pyridine) has a strong influence on their fluorescence properties and on their localization in living cells as they stain either the nucleus or mitochondria. Abstract : A convergent synthesis of various triphenylamine derivatives led to a small library of fluorophores showing different photophysical properties. The position of the pyridinium ( ortho, meta, para ) has an influence on the color of the fluorophore (from yellow to red) as well as on its cellular localization (mitochondria or nucleus).